Acneiform eruption developing with duloxetine: a case - Temizkan, Abdulgani; Korkmaz, Sevda; Demir, Betul; Atmaca, Murat (Yerkure Tanitim & Yayincilik Hizmetleri A S, 2016)
Duloxetine, serotonin and norepinephrine reuptake inhibitor is a strong antidepressant. It is widely used for generalized anxiety disorder, neuropathic pain and fibromyalgia syndrome as well as major depressive disorder. Its most important side effects are nausea, dryness of the mouth, constipation, sleep disorder, dizziness and fatigue. In this paper, we report a female patient who developed acneiform eruption due to duloxetine use, a different side effect than usual side effects.
Keywords: duloxetine; acneiform eruption; serotonin